PENINGKATAN MINAT DAN PENGUASAAN KONSEP MELALUI PEMBELAJARAN LEARNING CYCLE 5E - Yuca Aryanti; Ratu Betta Rudibyani; Tasviri Efkar (Universitas Lampung, 2013)
This study aims to obtain an effective instructional model increase interest and concept’s mastery of XI science in acid-base of Arrhenius material. The population are the class of XI Science SMA Al Azhar 3 Bandar Lampung with XI IPA 2 as experiment class and XI 4 as control. This research method is a quasi-experimental pretest posttest control group design. The research’s results showed the average value of the index gain interest in the control and experimental classes respectively 0,34 and 0,49; and the mean index gain mastery of concepts for the control and experimental classes respectively 0,33 and 0,55. Based on hypothesis testing, it was concluded that learning through the class with LC 5E has an interest and mastery of concepts that is higher than learning conventional class. This suggests that the learning material through LC 5E is more effective in increasing students' interest and mastery of concepts.Penelitian ini bertujuan untuk memperoleh model pembelajaran yang afektif dalam meningkatkan minat dan penguasaan konsep asam-basa Arrhenius. Populasi dalam penelitian ini adalah selurush siswa kelas XI IPA SMA Al Azhar 3 Bandar Lampung dengan kelas XI IPA 2 sebagai kelas eksperimen dan XI IPA 4 kelas control. Metode penelitan ni adalah kuasi eksperimen dengan non equivalent control group design. Hasil penelitian menunjukkan nilai rerata indeks gain minat untuk kelas control dan eksperimen masing-masing 0,34 dan 0,49; dan rerata indeks gain penguasaan konsep untuk kelas kontrol dan eksperimen masing-masing 0,33 dan 0,55. Berdasarkan uji hipotesis menunjukkan bahwa pembelajaran menggunakan LC 5E lebih tinggi daripada pembelajaran kon-vensional. Hal ini menunjukkan bahwa pembelajaran dengan LC 5E lebih efektif dalam me-ningkatkan minat dan penguasaaan konsep siswa.Kata kunci: Learning Cycle 5E (LC 5E), minat, penguasaan konsep